Teaching Beliefs of Graduate Students in Adult Education: A Longitudinal Perspective - Edward W. Taylor (Adult Education Research Conference, 2002)
This longitudinal study explores the influence on teaching beliefs from participating in a masters program in adult education. A group of practicing adult educators was interviewed over a two-year period while participating in graduate study. Findings reveal that graduate school had little impact on their prior teaching beliefs. Implications for graduate schools are discussed.